A PH multiplier-based PSO method for metal balance in nonferrous metal industry. Issue 21 (2018) - Ge, Minghe; Wang, Linqing; Lv, Zheng; Zhao, Jun
Abstract: Aiming at the problem of metal balance management in metallurgical enterprises, this paper presents an improved PSO method for data reconciliation technology. According to the actual production condition of the copper company, a least squares data reconciliation model is established, and a PH multiplier-based PSO optimization method is proposed for the characteristics of the model variable dimension and the constraint condition. This method first reduced the dimension of the problem due to the large size of the variable dimension, transformed the search of a large number of variables into several multipliers. And then the multipliers are searched by using PSO algorithm with faster search speed. The experiment shows that the method is efficient and the coordination result accords with the actual production.